KARAKTER SUMBERDAYA MANUSIA DAN PENGARUHNYA TERHADAP PEMASARAN BARANG PRODUKSI: STUDI KASUS PADA PENGRAJIN KULIT DI BANTUL YOGYAKARTA - Tugimin (Fakultas Bisnis Universitas Kristen Duta Wacana, 2015)
ABSTRACT The craft of a leather puppet in the district Bantul, Province Yogyakarta Special Region in its development experienced tides. Success retreival craft leather puppet skin strongly influenced by among other things, trend with the market demands quality goods, distinctness, value and price. But there is a vital need reckoned that human resources leather puppet characters handicraftsman skin also had an influence upon the way forward in sell their products. So far the role of the craftsman and forced them to market own goods their craft. Idealism character basic craftsman who pushes art of performing this function as artists and forced them role as an entrepreneur craft skin. It is very prevalent business does craft leather puppet skin and entrepreneurs craft leather puppet, eliciting much problem because tends perpetrated by player singular in do everything in good for production, management, marketing, etc. The development of crafts leather puppets are not limited on the orientation of the sheer capital adequacy but also the need for innovation, improvement of production systems, design, quality control, management, marketing system, that it took an understanding of entrepreneurship that is able to equip a small craftsmen as a good businessman. Keywords: character of human resources, marketing, business success. ABSTRAK Perkembangan kerajinan wayang kulit di Kabupaten Bantul, Propinsi Daerah Istimewa Yogyakarta cukup menyerap tenaga kerja. Keberhasilan usaha jenis ini perlu diimbangi dengan karakter sumber daya manusia dan kemampuan pegelolaan usaha yang baik agar dapat menangkap peluang pasar. Hanya saja selama ini sektor informal masih banyak kelemahannya karena para pengrajin merangkap kerja dalam segala urusan mulai dari pengerjaan produksi, manajemen, dan sekaligus pemasarannya, karena mereka belum memiliki pemahaman kewirausahaan yang baik. Untuk itulah perlu menjadi perhatian bersama agar sector ini dapat berkembang dengan baik untuk menangkap dan menjajagi pasar guna menjamin kelangsungan usahanya. Kata kunci: karakter pelaku usaha, pemasaran, keberhasilan usaha